Framework for ADS-B Performance Assessment: the London TMA Case Study - Ali, B.S.; Schuster, W.; Ochieng, W.; Majumdar, A.; Chiew, T.K. (Wiley, 2014)
This paper develops a comprehensive framework to evaluate ADS-B performance using the London Terminal Maneuvering Area (LTMA) as a case study. ADS-B data are from the CRISTAL project led by NATS UK. Performance is assessed in terms of accuracy, integrity, latency, availability and update rate. In the proposed framework, the Global Positioning System (GPS) data from the aircraft navigation system (obtained from British Airways) are used as the reference data to validate ADS-B performance. The results show that 66.7% of the aircraft provides horizontal position error less than 150 meters and latency of less than one second. Three aircraft provide wrong position integrity indicator categorized as missed detection. Finally, the update rate analysis shows inconsistent value for majority of the aircraft assessed, while the overall system availability is 81.78%. In addition, the key challenges in this analysis and errors identified in each dataset are also discussed in this paper.